Application of the flower of Beauveria bassiana Through immersion Seeds and It's effect on Colonization and content of Chlorophil leaves of red chilli (Capsicum annuum L.) - Magdalena , Saragih; Trizelia; Nurbailis; Yusniwati (Talenta Publisher, 2021)
Endophytic fungi in lately was getting a lot of attention in agriculture. Besides being able to increase plant resistance against plant pest organism, it has also the ability to stimulate germination and pant growth. One of endophytic fungi tested in its research was Beauveria bassiana from isolate Wheat, Coffeae, Cacao and entomopatogen fungus from Leptocorisa acuta insect. The aim of this research was to know the ability of Beauveria bassiana from some tested isolates and its effect on chlorophyll content of leaf chili followed Mack Kinner methode by doing seed treatment aplication. Colonization and chlorophyl content of chili leaf was done on 7 MPI. The research design used Random Block Design non factorial, data was analysis by 8 STAT. The result showed all of Beauveria bassiana isolates were able to colonize and established as endophytic in chili plant.Beauveria bassiana of wheat isolate was the best isolate giving spurring germination and seedling plant growth and not significant with B.bassiana isolate from Leptocorisa acuta insect. Aplication of B.bassiana isolates was able to increase the chlorophyll contentof chilileaf compared control. All of the tested B.bassiana fungus could increased chlorophyl-b content and chlorophyl totally of chili leaf, whereas chlorophyl-a content all of tested isolates was not significant. From its research showed there were corelation between colonization and leaf chlorophyll content, the higher percentage of endophytic fungus on leaf chili, it made higher the chlorophyl-b content and chlorophyl totally content of leaf chili.